Основные формулы логарифмов .

\( 1) \;\; \log_b a+\log_b c=\log_b {\; ac} \)

\( 2) \;\; \log_b a-\log_b c=\log_b {\; \frac{a}{c}} \)

\( 3) \;\; \log_b a^k=k \cdot \log_b a \)










1. Вычислить, применив формулу суммы логарифмов

\( \log_8 32 + \log_8 2 \)


  

\( 2 \)

\( \log_8 32 + \log_8 2 = \log_8 (32 \cdot 2 )=\log_8 64=2 \)

ПОЗЖЕ




2. Вычислить, применив формулу суммы логарифмов

\( \log_6 2 + \log_6 18 \)


  

\( 2 \)

\( \log_6 2 + \log_6 18 = \log_6 (2 \cdot 18)= \log_6 36=2 \)

ПОЗЖЕ




3. Вычислить, применив формулу суммы логарифмов

\( \log_3 13,5 + \log_3 2 \)


  

\( 3 \)

\( \log_3 13,5 + \log_3 2 = \log_3 27=3 \)

ПОЗЖЕ




4. Вычислить, применив формулу суммы логарифмов

\( \log_3 13,5 + \log_3 2 \)


  

\( 2 \)

\( \log_5 12,5 + \log_5 2 = \log_{15} (12,5 \cdot 2)= \log_5 25=2 \)

ПОЗЖЕ




5. Вычислить, применив формулу суммы логарифмов

\( \log_{15} 7,5 + \log_{15} 2 \)


  

\( 1 \)

\( \log_{15} 7,5 + \log_{15} 2 =\log_{15} (7,5 \cdot 2) =\log_{15} 15 =1 \)

ПОЗЖЕ




6. Вычислить, применив формулу суммы логарифмов

\( \log_{3} 1,5 + \log_{3} 6 \)


  

\( 2 \)

\( \log_{3} 1,5 + \log_{3} 6 = \log_{3} ( 1,5 \cdot 6 ) = \log_{3} 9=2 \)

ПОЗЖЕ




7. Вычислить, применив формулу суммы логарифмов

\( \log_{3} \; 48,6 + \log_{3} 5 \)


  

\( 5 \)

\( \log_{3} \; 48,6 + \log_{3} 5 = \log_{3} \; ( 48,6 \cdot 5 ) =\log_{3} 243=5 \)

ПОЗЖЕ




8. Вычислить, применив формулу суммы логарифмов

\( \log_{\frac{1}{3}} \; 0,2 + \log_{\frac{1}{3}} 5 \)


  

\( 0 \)

\( \log_{\frac{1}{3}} \; 0,2 + \log_{\frac{1}{3}} 5 = \log_{\frac{1}{3}} \; (0,2 \cdot 5)= \log_{\frac{1}{3}} \; 1=0 \)

ПОЗЖЕ




9. Вычислить, применив формулу суммы логарифмов

\( \log_{\frac{1}{13}} \; 0,25 + \log_{\frac{1}{13}} 4 \)


  

\( 0 \)

\( \log_{\frac{1}{13}} \; 0,25 + \log_{\frac{1}{13}} 4 = \log_{\frac{1}{13}} \; (0,25 \cdot 4)= \log_{\frac{1}{13}} \; 1=0 \)

ПОЗЖЕ




10. Вычислить, применив формулу суммы логарифмов

\( \log_{\frac{6}{35}} \; \frac{2}{7} + \log_{\frac{6}{35}} \; \frac{3}{5} \)


  

\( 1 \)

\( \log_{\frac{6}{35}} \; \frac{2}{7} + \log_{\frac{6}{35}} \; \frac{3}{5} = \log_{\frac{6}{35}} \; (\frac{2}{7} \cdot \frac{3}{5})= \log_{\frac{6}{35}} \; \frac{6}{35}=1 \)

ПОЗЖЕ